Analgesic management after thoracotomy for decortication in children: a retrospective audit of 83 children managed with a paravertebral infusion‐based regime. Issue 7 (5th May 2016) - Murphy, Tim; McCheyne, Alan; Karlsson, Jacob
Summary: Background: It is important that postoperative analgesic management after thoracotomy is very effective in order to optimize postoperative recovery. A regional technique such as an epidural or a paravertebral catheter with an infusion of local anesthetic may be supplemented with systemically administered analgesic drugs in order to achieve satisfactory analgesia. Objective: The objective of this observational study was to evaluate whether a paravertebral infusion of local anesthetic delivered via a surgically placed catheter together with systemic analgesics is associated with low pain scores and satisfactory analgesia after thoracotomy for decortication in children. Methods: We performed a retrospective analysis of the notes and charts of 83 children admitted with empyema thoracis and managed with thoracotomy and decortication. We collected data on the doses of analgesic drugs (morphine, paracetamol, and ibuprofen) and details of paravertebral infusions, together with postoperative pain scores for the first 48 h after surgery, or earlier if the paravertebral infusion was stopped within 48 h of surgery. Poor quality analgesia was defined as a score of 7 or more on the Visual Analog/Smiley Faces Scale ('VAS/SF'). Results: A total of 81 children were ASA 1 status and two were ASA 3 status. Analgesia comprised intravenous morphine at a mean dose of 20 μg·kg −1 ·h −1, together with oral paracetamol (62.5 mg·kg −1 /24 h) and ibuprofen (14.2 mg·kg −1 /24 h). The mean paravertebral bupivacaine dose was 0.29 mg·kg −1 ·h −1 . Sixty‐four patients (77.1%) had good quality analgesia, 17 (20.5%) patients had moderate quality analgesia, and only two patients (2.4%) had poor quality analgesia. Conclusion: Analgesic outcomes with this regimen appear to be very satisfactory. It compares favorably with an epidural‐based regimen. Abstract :